The The Analyse of Barton Pendulum for Application of Resonance Experiment for Senior High School Student - ALBAB, ALFI NUR; Evita, Maria; Aminah, Nina Siti; Irvianto, Berlian Oka (Institut Teknologi Bandung, 2025)
While pendulums have been around for thousands of years and have even been successfully incorporated into high school curricula, they are still minimally used in Physics experiments on resonance materials. In this study, we designed the Barton Pendulum as a simple laboratory kit operated by teachers and easily observed by students. The pendulum system consists of a series of objects and a small ball connected and suspended with a carbolic string. The small ball here is none other than the trigger that makes all objects oscillate. As an observation material, the length of the string for each object is made different (40 cm, 29.8 cm, 20 cm, 9.5 cm, 6.7 cm). The period of each object in the system is observed using a stopwatch so that the oscillation frequency of each object is known. The object that resonates with the ball is the object that has the same length as the length of the hanging string of the ball, which means that this object has the same natural frequency as the frequency of the ball. The phase difference between the object and the trigger is also observed. The phase difference is equal to rad for objects with a string length equal to the length of the trigger string, and the phase difference is equal to π rad for objects with a string length longer than the length of the trigger.